2015
DOI: 10.15640/ijgws.v3n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Findings of a Study Exploring Homeless Street Females in Addis Ababa, Ethiopia: A Need for Community Based Programs

Abstract: A qualitative research design using the interviews of five homeless street females was undertaken to understand the meaning of the lived experiences of the homeless street females and their identified need for community based programs. This research design provided the researchers with the opportunity to understand the complexities of homelessness from the homeless street females in Ethiopia using ethnography. The qualitative study was exploratory in nature and utilized ethnographic methods, such as participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
4
9
0
Order By: Relevance
“…Findings of our study conform to those of studies conducted in big cities in Ethiopia. The factors associated with causation of homelessness among women in previous studies in Ethiopia were also identified in our study; those factors were migration, urbanization, poverty, abuse, escape from child marriage, unemployment, death of one or both parents, divorce of parents, pregnancy out of wedlock, and abandonment by spouse [ 14 , 15 , 29 , 30 ]. This shows the existence of factors which are similar throughout Ethiopian cities.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Findings of our study conform to those of studies conducted in big cities in Ethiopia. The factors associated with causation of homelessness among women in previous studies in Ethiopia were also identified in our study; those factors were migration, urbanization, poverty, abuse, escape from child marriage, unemployment, death of one or both parents, divorce of parents, pregnancy out of wedlock, and abandonment by spouse [ 14 , 15 , 29 , 30 ]. This shows the existence of factors which are similar throughout Ethiopian cities.…”
Section: Discussionsupporting
confidence: 59%
“…‘Hidden homelessness’ is a good example for homelessness by way of ‘houselessness’ or ‘insecure accommodation.’ The hidden homeless population of women comprises those who double up with friends or family, or those staying at rooming houses or hotels [ 13 ]. Studies conducted in Ethiopia used the word ‘homelessness’ to refer to those who were ‘roofless’ or ‘street homeless’ [ 14 16 ]. A previous study conducted in Addis Ababa used the definition of homeless as ‘those sleeping in designated shelters or public spaces’.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations